Smart City Policy: Strategy and Implementation to Realize Smart Urban Governance in Indonesia - Tri Sulistyaningsih; Rika Ayu Purnama; Umi Kulsum (Universitas Muhammadiyah Yogyakarta, 2023)
This paper delves into the intricate landscape of Smart City policies, strategies, and implementation challenges in Indonesia, with a particular emphasis on smart urban governance. Despite significant global discourse, the formulation and execution of Smart City initiatives in Indonesia remain fragmented, resulting in inconsistencies across governance frameworks. To address these gaps, this study systematically analyzes 213 Scopus-indexed articles on